HUBUNGAN MENGKONSUMSI KOPI DENGAN TERJADINYA LOW BACK PAIN PADA LANSIA DI PANTI JUMPO ULEE KARENG - Aditya Candra; Hady Maulanza (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2021)
Based of the problem in this Research is to determine whether there are connection coffee consumption for thinking about incidence of low back pain (LBP) in the elderly at Panti Jumpo Ulee Kareng. The purpose of this research is to obtain information about connection coffee consumption and the incidence of LBP in the elderly at Panti Jumpo Ulee Kareng. Analitical method that used in this research objectives, the population of this research was 50 people. The data analysis method used Chi Square (X2) and this research were did from January - May 2019. The results showed that there was no significant relationship between drinking coffee and the occurrence of LBP in the elderly Panti Jumpo Ulee Kareng. It was found that the sample who had consumption habits based on gender were 19 people (38%) while those who did not experience LBP based on gender were 31 people (62%). In addition, other results show that 19 people (38%) have experienced LBP by age, while 31 people (62%) have not experienced LBP. Then by investigating what led to the relationship, drinking coffee with the LBP incidence studied by the researcher was 19 people (38%) while 31 people (62%) did not experience LBP. The results of research indicate that there is no relationship between cunsumption coffee and the incidence of LBP in the elderly at Panti Jumpo Ulee Kareng (P-value 0.0153). The results of this research, the researchers concluded that there was no significant relationship between drinking coffee and LBP in Ulee Kareng elderly.Keywords: Coffee Drinking Habit, Low Back Pain, Elderly